WORST_CASE(Omega(0),?) Initial ITS Start location: l3 0: l0 -> l1 : y^0'=y^post0, x^0'=x^post0, (-x^post0+x^0 == 0 /\ 1-y^0 <= 0 /\ -y^post0+y^0 == 0 /\ 1-x^0 <= 0), cost: 1 1: l1 -> l0 : y^0'=y^post1, x^0'=x^post1, (0 == 0 /\ 1-y^0+y^post1 == 0), cost: 1 2: l1 -> l0 : y^0'=y^post2, x^0'=x^post2, (1-x^0+x^post2 == 0 /\ y^0-y^post2 == 0), cost: 1 3: l2 -> l0 : y^0'=y^post3, x^0'=x^post3, (y^0-y^post3 == 0 /\ -x^post3+x^0 == 0), cost: 1 4: l3 -> l2 : y^0'=y^post4, x^0'=x^post4, (y^0-y^post4 == 0 /\ x^0-x^post4 == 0), cost: 1 Applied preprocessing Original rule: l0 -> l1 : y^0'=y^post0, x^0'=x^post0, (-x^post0+x^0 == 0 /\ 1-y^0 <= 0 /\ -y^post0+y^0 == 0 /\ 1-x^0 <= 0), cost: 1 New rule: l0 -> l1 : (-1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 1 Applied preprocessing Original rule: l1 -> l0 : y^0'=y^post1, x^0'=x^post1, (0 == 0 /\ 1-y^0+y^post1 == 0), cost: 1 New rule: l1 -> l0 : y^0'=-1+y^0, x^0'=x^post1, 0 == 0, cost: 1 Applied preprocessing Original rule: l1 -> l0 : y^0'=y^post2, x^0'=x^post2, (1-x^0+x^post2 == 0 /\ y^0-y^post2 == 0), cost: 1 New rule: l1 -> l0 : x^0'=-1+x^0, TRUE, cost: 1 Applied preprocessing Original rule: l2 -> l0 : y^0'=y^post3, x^0'=x^post3, (y^0-y^post3 == 0 /\ -x^post3+x^0 == 0), cost: 1 New rule: l2 -> l0 : TRUE, cost: 1 Applied preprocessing Original rule: l3 -> l2 : y^0'=y^post4, x^0'=x^post4, (y^0-y^post4 == 0 /\ x^0-x^post4 == 0), cost: 1 New rule: l3 -> l2 : TRUE, cost: 1 Simplified rules Start location: l3 5: l0 -> l1 : (-1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 1 6: l1 -> l0 : y^0'=-1+y^0, x^0'=x^post1, 0 == 0, cost: 1 7: l1 -> l0 : x^0'=-1+x^0, TRUE, cost: 1 8: l2 -> l0 : TRUE, cost: 1 9: l3 -> l2 : TRUE, cost: 1 Eliminating location l2 by chaining: Applied chaining First rule: l3 -> l2 : TRUE, cost: 1 Second rule: l2 -> l0 : TRUE, cost: 1 New rule: l3 -> l0 : TRUE, cost: 2 Applied deletion Removed the following rules: 8 9 Eliminated locations on linear paths Start location: l3 5: l0 -> l1 : (-1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 1 6: l1 -> l0 : y^0'=-1+y^0, x^0'=x^post1, 0 == 0, cost: 1 7: l1 -> l0 : x^0'=-1+x^0, TRUE, cost: 1 10: l3 -> l0 : TRUE, cost: 2 Eliminating location l1 by chaining: Applied chaining First rule: l0 -> l1 : (-1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 1 Second rule: l1 -> l0 : y^0'=-1+y^0, x^0'=x^post1, 0 == 0, cost: 1 New rule: l0 -> l0 : y^0'=-1+y^0, x^0'=x^post1, (0 == 0 /\ -1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2 Applied simplification Original rule: l0 -> l0 : y^0'=-1+y^0, x^0'=x^post1, (0 == 0 /\ -1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2 New rule: l0 -> l0 : y^0'=-1+y^0, x^0'=x^post1, (-1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2 Applied chaining First rule: l0 -> l1 : (-1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 1 Second rule: l1 -> l0 : x^0'=-1+x^0, TRUE, cost: 1 New rule: l0 -> l0 : x^0'=-1+x^0, (-1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2 Applied deletion Removed the following rules: 5 6 7 Eliminated locations on tree-shaped paths Start location: l3 11: l0 -> l0 : y^0'=-1+y^0, x^0'=x^post1, (-1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2 12: l0 -> l0 : x^0'=-1+x^0, (-1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2 10: l3 -> l0 : TRUE, cost: 2 Applied acceleration Original rule: l0 -> l0 : y^0'=-1+y^0, x^0'=x^post1, (-1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2 New rule: l0 -> l0 : y^0'=y^0-n, x^0'=x^post1, (-1+x^post1 >= 0 /\ y^0-n >= 0 /\ -1+n >= 0 /\ -1+x^0 >= 0), cost: 2*n Sub-proof via acceration calculus written to file:///tmp/tmpnam_KhFoOf.txt Applied instantiation Original rule: l0 -> l0 : y^0'=y^0-n, x^0'=x^post1, (-1+x^post1 >= 0 /\ y^0-n >= 0 /\ -1+n >= 0 /\ -1+x^0 >= 0), cost: 2*n New rule: l0 -> l0 : y^0'=0, x^0'=x^post1, (0 >= 0 /\ -1+x^post1 >= 0 /\ -1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2*y^0 Applied acceleration Original rule: l0 -> l0 : x^0'=-1+x^0, (-1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2 New rule: l0 -> l0 : x^0'=-n0+x^0, (n0 >= 0 /\ -n0+x^0 >= 0 /\ -1+y^0 >= 0), cost: 2*n0 Sub-proof via acceration calculus written to file:///tmp/tmpnam_mLoeGH.txt Applied instantiation Original rule: l0 -> l0 : x^0'=-n0+x^0, (n0 >= 0 /\ -n0+x^0 >= 0 /\ -1+y^0 >= 0), cost: 2*n0 New rule: l0 -> l0 : x^0'=0, (0 >= 0 /\ x^0 >= 0 /\ -1+y^0 >= 0), cost: 2*x^0 Applied simplification Original rule: l0 -> l0 : y^0'=0, x^0'=x^post1, (0 >= 0 /\ -1+x^post1 >= 0 /\ -1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2*y^0 New rule: l0 -> l0 : y^0'=0, x^0'=x^post1, (-1+x^post1 >= 0 /\ -1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2*y^0 Applied simplification Original rule: l0 -> l0 : x^0'=0, (0 >= 0 /\ x^0 >= 0 /\ -1+y^0 >= 0), cost: 2*x^0 New rule: l0 -> l0 : x^0'=0, (x^0 >= 0 /\ -1+y^0 >= 0), cost: 2*x^0 Applied deletion Removed the following rules: 11 12 Accelerated simple loops Start location: l3 15: l0 -> l0 : y^0'=0, x^0'=x^post1, (-1+x^post1 >= 0 /\ -1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2*y^0 16: l0 -> l0 : x^0'=0, (x^0 >= 0 /\ -1+y^0 >= 0), cost: 2*x^0 10: l3 -> l0 : TRUE, cost: 2 Applied chaining First rule: l3 -> l0 : TRUE, cost: 2 Second rule: l0 -> l0 : y^0'=0, x^0'=x^post1, (-1+x^post1 >= 0 /\ -1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2*y^0 New rule: l3 -> l0 : y^0'=0, x^0'=x^post1, (-1+x^post1 >= 0 /\ -1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2+2*y^0 Applied chaining First rule: l3 -> l0 : TRUE, cost: 2 Second rule: l0 -> l0 : x^0'=0, (x^0 >= 0 /\ -1+y^0 >= 0), cost: 2*x^0 New rule: l3 -> l0 : x^0'=0, (x^0 >= 0 /\ -1+y^0 >= 0), cost: 2+2*x^0 Applied deletion Removed the following rules: 15 16 Chained accelerated rules with incoming rules Start location: l3 10: l3 -> l0 : TRUE, cost: 2 17: l3 -> l0 : y^0'=0, x^0'=x^post1, (-1+x^post1 >= 0 /\ -1+y^0 >= 0 /\ -1+x^0 >= 0), cost: 2+2*y^0 18: l3 -> l0 : x^0'=0, (x^0 >= 0 /\ -1+y^0 >= 0), cost: 2+2*x^0 Removed unreachable locations and irrelevant leafs Start location: l3 Computing asymptotic complexity Proved the following lower bound Complexity: Unknown Cpx degree: ? Solved cost: 0 Rule cost: 0